If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + 5 = 3 + 5y Reorder the terms: 5 + 9y = 3 + 5y Solving 5 + 9y = 3 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 5 + 9y + -5y = 3 + 5y + -5y Combine like terms: 9y + -5y = 4y 5 + 4y = 3 + 5y + -5y Combine like terms: 5y + -5y = 0 5 + 4y = 3 + 0 5 + 4y = 3 Add '-5' to each side of the equation. 5 + -5 + 4y = 3 + -5 Combine like terms: 5 + -5 = 0 0 + 4y = 3 + -5 4y = 3 + -5 Combine like terms: 3 + -5 = -2 4y = -2 Divide each side by '4'. y = -0.5 Simplifying y = -0.5
| 5x-3-32=10x | | 2+9+3=45 | | 6n-8-n=-18 | | 2x(x-12)=-40 | | 2x+4x+5-15=4x-20+50 | | 4n-3n=-8 | | 3x^2+2x=12-7x | | 9n-8=64 | | x+37=78 | | d=5r+8w | | -4(x+1)-11=13+8 | | 4x+6=54 | | 4+3k-1=6 | | p^2-9=0 | | 7-4x-3=20 | | 71=9e^3x | | x+22+3x=-28-3x-34 | | 10x^2-9x+6=0 | | 1+b-7b=-5 | | 7+-8-2=-3 | | 2m-3m=5 | | 20-5x=14+x | | 2x-5x(10-6)=3x-10+4x | | -2(2x-3)=-12 | | 1-6b-6=-5 | | 4m+6m=0 | | 4x+4=3x+7 | | 8y-8x=5 | | (x-7)(5x+1)=0 | | 2r-3*3=3.5 | | -4-7x+3x=-16 | | 6x-y=-7 |